Educational inequalities and premature mortality: the Cuba Prospective Study - Ross, S; Armas Rojas, N; Sawatzky, J; Varona-Pérez, P; Burrett, JA; Calderón Martínez, M; Lorenzo-Vázquez, E; Constantén, SB; Sherliker, P; Rigau, JMM; López, OJH; Morales, MÁM; et al. (Elsevier, 2022)
Background Although socioeconomic status is a major determinant of premature mortality in many populations, the impact of social inequalities on premature mortality in Cuba, a country with universal education and health care, remains unclear. We aimed to assess the association between educational level and premature adult mortality in Cuba. Methods The Cuba Prospective Study (a cohort study) enrolled 146 556 adults aged 30 years and older from the general population in five provinces from Jan 1, 1996, to Nov 24, 2002. Participants were followed up until Jan 1, 2017, for cause-specific mortality. Deaths were identified through linkage to the Cuban Public Health Ministry's national mortality records. Cox regression models yielded rate ratios (RRs) for the effect of educational level (a commonly used measure for social status) on mortality at ages 35–74 years, with assessment for the mediating effects of smoking, alcohol consumption, and BMI. Findings A total of 127 273 participants aged 35–74 years were included in the analyses. There was a strong inverse association between educational level and premature mortality. Compared with a university education, men who did not complete primary education had an approximately 60% higher risk of premature mortality (RR 1·55, 95% CI 1·40–1·72), while the risk was approximately doubled in women (1·96, 1·81–2·13). Overall, 28% of premature deaths could be attributed to lower education levels. Excess mortality in women was primarily due to vascular disease, while vascular disease and cancer were equally important in men. 31% of the association with education in men and 18% in women could be explained by common modifiable risk factors, with smoking having the largest effect. Interpretation This study highlights the value of understanding the determinants of health inequalities in different populations. Although many major determinants lie outside the health system in Cuba, this study has identified the diseases and risk factors that require targeted public health interventions, particularly smoking. Funding UK Medical Research Council, British Heart Foundation, Cancer Research UK, CDC Foundation (with support from Amgen).